Non-catalyzed addition of secondary phosphine chalcogenides to divinyl chalcogenides under solvent-free conditions. (2nd September 2016) - Gusarova, Nina K.; Chernysheva, Nataliya A.; Yas'ko, Svetlana V.; Klyba, Lyudmila V.; Trofimov, Boris A.
ABSTRACT: Secondary phosphine chalcogenides, R2 PX (R═(CH2 )2 Ph, Ph; X = S, Se), react with divinyl chalcogenides, (CH2 ═CH)2 Y (Y = S, Se, Te), at the 2:1 molar ratio (80–82°C, 56–80 h) in the absence of both catalysts (initiators) and solvents to quantitatively afford the corresponding anti-Markovnikov diadducts. Even at the equimolar reactant ratio, the diadducts are the major products, though monoadducts are also formed. When Y = Te, vinylphosphine chalcogenides and metal Te are obtained, thus showing that divinyl telluride behaves as the vinylating agent. GRAPHICAL ABSTRACT: